ADDITION OF CARRAGENAN (Eucheuma cottonii) TO PREFERENCES MEATBALLS OF RUBY SNAPPER (Nemipterus japonicu) - Arif, Galih Anugrah Firman; Sipahutar, Yuliati H (Politeknik Kelautan dan Perikanan Dumai, 2023)
Meatballs are a typical Indonesian food that is very popular and quite popular with both children and adults, which is known to use dangerous chewy ingredients. This research was conducted to to determine the addition of carrageenan to the level of preference for nemipterid fish meatballs. The experimental method was carried out using a completely randomized design (CRD) with five treatments adding 0%, 1%, 2%, 3% and 4% carrageenan to the amount of nemipterip fish meat (w/w) and 30 panelists as replicates. Sensory data analysis with Kruskal Wallis if the resultsare significantly different (p < 0.05) followed by a Multiple Comparison Test. The preferred meatballs are followed by chemical testing (moisture content, ash content, fat content, protein content) and microbiological tests for ALT, Salmonella and Escherichia coli. The results showed that the addition ofi carrageenan had a significant effect on the hedonic value with the appearance and texture parameters, while the taste and smell values had no significant effect. The results of the meatballs that consumers like are the addition of carrageenan by 3%, with an appearance value of 8.36, an odor of 7.65, a taste of 7.63, a texture of 8.48, and a chemical value of 72.13% water content, 0.79% ash content, 9.66% protein content, 1.58% fat content . ALT 5.1 × 103 colonies/g, negative Escherichia coli and negative Salmonella. These results indicate that the texture nemipterid fish meatballs can be improved by adding carrageenan as a substitute for a chewing agent.